THE ROLE OF EMOTIVE VERBS IN LITERATURE AND LINGUISTICS - Kurvonbekov Manuchexr Islomjon ugli (Bright Mind Publishing, 2025)
This article explores the role of emotive verbs in literature and linguistics, emphasizing their significance in expressing and analyzing emotions through language. Emotive verbs, such as love, hate, and fear, are integral in shaping narrative tone and character depth in literary texts, while also providing valuable data for linguistic analysis of emotional discourse.
Keywords: Emotive verbs, literature, linguistics, emotional expression, discourse analysis, stylistics, corpus analysis, character development.